The Right to Be Punished Modern Doctrinal Sentencing - Hallevy, Gabriel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Does an offender have the right to be punished? "The right to be punished" may sound like an oxymoron, but it is not necessarily so. With the emergence of modern criminal law, the offender gained the right to be punished by rational criminal law rather than being lynched by an angry mob. The present-day offender may have the right to be punished by doctrinal sentencing rather than being subjected to verdicts based on vague, unclear, and uncertain principles. In modern criminal law, the imposition of criminal liability follows accurate and strict rules, whereas there are no similar rules for the imposition of punishment. The process of sentencing is vague and obscure, as are the considerations used for the imposition of punishments. The objective of the present book is to propose a comprehensive, general, and legally sophisticated theory of modern doctrinal sentencing. The challenges of such a legal theory are plenty and complex. In addition to increasing clarity and certainty, modern doctrinal sentencing must deal with modern types of delinquency (e.g. organized crime, recidivism, corporate offenders, high-tech offenses, etc.) and modern principles of criminal law. Modern doctrinal sentencing must serve to ensure optimal sentencing.
Punishment as Part of Modern Criminal Law Theory -- General Purposes of Punishment -- General Considerations of Punishment -- General Structure of Doctrinal Sentencing -- Physical Punishments -- Economic Punishments -- Conclusion.
Keywords: Law; Philosophy of law; Constitutional law; Criminology; Law; International Criminal Law; Theories of Law, Philosophy of Law, Legal History; Criminology & Criminal Justice; Human Rights; Philosophy of Law; Constitutional Law